2011
DOI: 10.1177/0146621610390674
|View full text |Cite
|
Sign up to set email alerts
|

Fitting IRT Models to Dichotomous and Polytomous Data: Assessing the Relative Model–Data Fit of Ideal Point and Dominance Models

Abstract: This study investigated the relative model-data fit of an ideal point item response theory (IRT) model (the generalized graded unfolding model [GGUM]) and dominance IRT models (e.g., the two-parameter logistic model [2PLM] and Samejima's graded response model [GRM]) to simulated dichotomous and polytomous data generated from each of these models. The relative magnitudes of the adjusted c 2 /df ratios for item pairs and item triples at the test level were used to evaluate fit. Two simulation studies were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 34 publications
5
40
0
Order By: Relevance
“…This is consistent with past research that has shown slightly better fit for the 2-parameter logistic model (a special case of the GRM) compared to the GGUM for doubles and triples for some personality measures when item singles suggest better fit for the GGUM (see Stark et al, 2006). Moreover, as noted previously, the 2 /df ratios Ͻ 3 criterion has been shown to be inappropriate for doubles and triples (Tay et al, 2011). As can be seen in Figure 5, the information function for the GRM and GGUM showed higher reliability at the low end of the continuum versus the high end but relatively low reliability at higher levels.…”
Section: Study 2 Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with past research that has shown slightly better fit for the 2-parameter logistic model (a special case of the GRM) compared to the GGUM for doubles and triples for some personality measures when item singles suggest better fit for the GGUM (see Stark et al, 2006). Moreover, as noted previously, the 2 /df ratios Ͻ 3 criterion has been shown to be inappropriate for doubles and triples (Tay et al, 2011). As can be seen in Figure 5, the information function for the GRM and GGUM showed higher reliability at the low end of the continuum versus the high end but relatively low reliability at higher levels.…”
Section: Study 2 Methodssupporting
confidence: 90%
“…Doubles and triples showed means larger than the suggested cutoff of 3, suggesting some potential problems with local dependence, an issue addressed in more detail later in this section. However, it has been recently suggested (Tay, Ali, Drasgow, & Williams, 2011) that the 2 /df ratios Ͻ 3 criterion is inappropriate for doubles and triples, and these results are consistent with past IRT model-data fit analyses of personality measures (e.g., see Stark et al, 2006). Given these results, we concluded that person parameters would be well-interpreted and continued with our substantive analyses.…”
Section: Study 1 Methodssupporting
confidence: 89%
“…As previously stated, the application of dominance IRT models requires reverse scoring, where this is not the case for unfolding models. Following established analytic procedures ( Tay et al, 2011 ) negatively valenced items were reverse coded first.…”
Section: Methodsmentioning
confidence: 99%
“…We compared the relative fit of the ideal point and dominance models with the adjusted χ 2 /df ( Tay et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…The generation of model-fitting data closely followed previous research based on the GGUM (Roberts, Donoghue, & Laughlin, 2002;Tay, Ali, Drasgow, & Williams, 2011;Wang, Tay, & Drasgow, 2013). Item scores were randomly drawn from multinomial distributions based on the conditional probabilities given by Equation 1.…”
Section: Simulation Studymentioning
confidence: 99%